Nonlinear and Nonparametric Causal Relationship Between Financial Inclusion, Energy Efciency, and Sustainable Environment in Developed Economies - Qiaoqi, Lang; Asadullah, Khaskheli; Syed Ali, Raza; Komal Akram, Khan; Puah, Chin Hong (Springer Nature, 2024)
A sustainable environment is as important as the economy’s growth, but, unfortunately, economic growth is environmentally unsustainable. Hence, there is a need to adopt efcient ways to help maintain a sustainable environment. The present research is designed to evaluate the association between fnancial inclusion, energy efciency, and a sustainable environment in developed economies. The World Bank has regarded fnancial inclusion as a crucial element for attaining seven Sustainable Development Goals. So, there is a need to examine the causal association between fnancial inclusion, energy efciency, and a sustainable environment. We employed the linear Granger causality test, Brock-Dechert-Scheinkman test for nonlinearity, and parameter stability testing. These techniques confrmed the presence of a nonlinear association and structural breaks between proposed variables. Later, the nonparametric causality in the quantiles technique has been employed for the analysis. The fndings reveal that fnancial inclusions play a crucial role in maintaining a sustainable environment, but it is necessary to adopt energy efciency policies to mitigate emissions. Furthermore, the recommendations for policymakers, government, and future scholars are discussed in the paper.